Pathologies of the Poor: What do the War on Drugs and Welfare Reform Have in Common? - Amundson, Kalynn (2014)
The Personal Responsibility and Work Opportunity Reconciliation Act of 1996 (PRWORA) authorized drug testing of welfare recipients as a criterion for assistance eligibility. This raises the question of a possible confluence of War on Drugs and Welfare Reform policies, as indicated by continuity in policymakers’ rhetoric. We examine federal-level policymakers’ debates surrounding the authorization of drug testing welfare recipients. The analysis reveals that themes of social pathology were present in both policy areas. Crime, drug addiction, welfare dependency, and drug testing themes are comparable in both debates. Teen pregnancy, out-of-wedlock birth, and female-headed households themes were more prevalent in Welfare Reform debates, with the exception of drug-addicted newborns, which crossed both policy streams